Correction: Pre-exposure prophylaxis (PrEP) awareness, use, and discontinuation among Lake Victoria fisherfolk in Uganda: A cross-sectional population-based study. - PLOS Global Public Health Staff (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003994.].